Irradiated patients and survival rate of dental implants: A systematic review and meta-analysis - Nobrega, Adhara Smith [UNESP]; Santiago, Joel Ferreira; Faria Almeida, Daniel Augusto de; Santos, Daniela Micheline dos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP] (Elsevier B.V., 2016)
Statement of problem. Radiotherapy has been considered a contraindication for rehabilitation with dental implants because it can change the survival rate of implants. Nevertheless, the installation of implants in irradiated patients has been used with varying success. Purpose. The purpose of this systematic review was to compare the success rate of implants placed in irradiated human bone tissue with that of implants placed in nonirradiated areas. Material and methods. Searches were performed in the EMBASE, Cochrane, and PubMed/Medline databases up to December 2013 to identify clinical trials addressing the subject. This systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines. The relative risks of implant failure and survival curves were calculated considering a confidence interval of 95%. Heterogeneity was analyzed by using a funnel chart. Results. A total of 40 studies involving 2220 participants and 9231 dental implants were selected. The survival curve of the studies indicated a survival rate of 84.3% for implants installed in irradiated bone tissue. The meta-analysis indicated statistically significant differences (P<.001) between item success rates of implants placed in irradiated areas and those of implants placed in nonirradiated areas. Conclusions. Dental implants installed in the irradiated area of an oral cavity have a high survival rate, but strict monitoring is needed to prevent complications, thereby reducing possible failures.